Handbook Of Climate Change And Agroecosystems Climate Change And Farming System Planning In Africa And South Asia: Agmip Stakeholder-driven Research (In 2 Parts) - Rosenzweig, Cynthia; Mutter, Carolyn Z.; Mencos Contreras, Erik (Series On Climate Change Impacts, Adaptation, And Mitigation, 2021)
This two-part handbook focuses on the work that the Agricultural Model Intercomparison and Improvement Project (AgMIP) accomplished using a new method - the AgMIP Regional Integrated Assessment Protocol - in Sub-Saharan Africa (SSA) and South Asia (SA), with funding from the UK Department for International Development. Through this research, AgMIP substantially improves the characterization and understanding of food security in SSA and SA and how its affected by climate variability and change.The chapters in this handbook demonstrate how AgMIP has enhanced the capacity of developing country researchers and stakeholders to work together, exploring and prioritizing adaptation to current and future climate stresses. Part 1 describes regional integrated assessment methods and analyses, while Part 2 presents the outcomes of farming system studies. The entire volume shows how AgMIP has established, as a public good, protocols for Regional Integrated Assessments that improve the capability of developing countries to address climate change challenges.Related Link(s)